First descriptions of immatures for Megistops (Boheman) (Coleoptera, Chrysomelidae, Galerucinae) in a new host-plant family, with notes on life history and redescription of M. vandepolli Duvivier - Linzmeier, Adelita M.; Ribeiro-Costa, Cibele S.; de A. Moura, Luciano (Zootaxa, 2007)
The adult of Megistops vandepolli Duvivier is redescribed and previously undescribed features such as mouth parts, wing venation and genitalia are included. Egg, mature larva and pupa are described and illustrated for the first time providing data for future phylogenetic studies in Galerucinae. Megistops vandepolli is found in Buddleja stachyoides Cham. & Schltdl (Buddlejaceae); their larvae are leaf-miners and the pupation occurs in soil. Additional comments on its life history are also presented and discussed. The genus Megistops (Boheman) is added to this list of Alticini leaf-miners and a new family of host-plant is recorded for it.